Anchored atomic Ru-O4 architecture enables ultra-effective Fe(VI) activation via avoiding Fe(VI) self-decay for water purification - Yundan Chen; Xiaofei Ge; Jun Li; Zishuai Bill Zhang; Zhenshan Li (Nature Communications)
Abstract Ferrate (Fe(VI)) is a prospective green oxidant owing to producing highly reactive Fe(IV)/Fe(V) for micropollutant degradation. However, the performance is significantly compromised by the severe side reaction of Fe(VI) self-decay with H2O, generating H2O2 byproduct that quickly quenches Fe(IV)/Fe(V). In this study, we synthesized a single-ruthenium-atom catalyst (RuGN) to activate Fe(VI) to selectively produce Fe(IV)/Fe(V)/Ru(V) for antibiotic degradation, with record-fast ciprofloxacin (CIP) degradation kinetics (~18.7 min−1 g−1 L). Since Fe(VI) preferentially reacts with RuGN rather than H2O, RuGN inhibits Fe(VI) self-decay, thus decreasing the H2O2 production. Moreover, RuGN consumes H2O2 (that quenches Fe(IV)/Fe(V)/Ru(V)) in the reaction system, which significantly improves the Fe(VI) utilization rate. Compared with other typical transition metal single-atom catalysts, RuGN exhibits moderate interactions with Fe(VI) and thus facilitates the electron transfer via Ru-O-Fe coordination to activate Fe(VI) for efficient CIP degradation. The RuGN/Fe(VI) system resists interference from background substances coexisting in water, achieving efficient CIP degradation under complex water chemistry conditions and in real water samples. The system can also efficiently degrade CIP in continuous-flow reactors. This work develops a promising strategy for improving Fe(VI) activation via regulating the interaction between the metal site and Fe(VI), holding immense potential for deep wastewater purification.